1997
DOI: 10.2307/3433066
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Hexachlorobenzene in Humans: Association between Serum Levels and Urinary Metabolites in a Highly Exposed Population

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…A strong correlation between internal dose of HCB and the formation of mercapturic acid derivatives in urine was found in a previous study 18. The formation of glutathione conjugates may play a significant part in HCB detoxification within this range of human accumulation of HCB.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A strong correlation between internal dose of HCB and the formation of mercapturic acid derivatives in urine was found in a previous study 18. The formation of glutathione conjugates may play a significant part in HCB detoxification within this range of human accumulation of HCB.…”
Section: Discussionsupporting
confidence: 69%
“…No differences in socioeconomic, occupational, and health status, nor in HCB concentrations, were found between subjects from the random samples and volunteers. Concentrations of HCB in serum were analyzed in all samples by gas chromatography coupled to electron capture detection (GC-ECD) as previously described 18. Polychlorobiphenyls (summation of 28, 52, 101, 118, 138, 153, and 180 congeners) were also assessed due to their potential effects on thyroid and liver enzymes.…”
Section: Population and Methodsmentioning
confidence: 99%
“…Total porphyrins were analysed in 604 of these participants [11], a subsample of 241 of them being included in the present study. This subsample was composed of a 100 subjects previously selected for the studies of HCB biokinetics [15] consisting of those 8 subjects with the four highest and four lowest HCB levels, complemented by a random sample of 92, supplemented by a further 141 subjects who had worked in the electrochemical factory. Workers were included because they had the highest levels of HCB in Flix [10].…”
Section: Methodsmentioning
confidence: 99%
“…All the analyses were carried out in the Department of Environmental Chemistry (CID-CSIC). Details of the methodology have been reported elsewhere [10,15]. We present results for the most prevalent compounds found in sera samples: HCB, dichlorodiphenyl dichloroethene ( p,p' -DDE), and polychlorinated biphenyls (PCBs) which we present as the summation of the individual congeners 28, 52, 101, 118, 138,153, and 180.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that metabolism of HCB mediated by glutathion was higher in men than in women. 29 Few studies have assessed diVerences in organochlorine concentrations by sex, partly because most of the studies have been done only on women. In other studies no consistent diVerences have been reported, 24 30 but failure to adjust for occupation may explain part of these inconsistencies.…”
Section: Concentrations Of -Hch Pp'-dde Andmentioning
confidence: 99%